Avaliação da polpa dentária de ratos após pulpotomia e selamento pulpar com uma pasta à base de Anadenanthera colubrina (Vell.) Brenan E. com a pasta antibiótica CTZ - Santos, Carlus Alberto Oliveira dos (2020)
Different materials are indicated for pulp sealing after the pulpotomy of primary teeth, however, there is no scientific evidence to support the superiority of one medication over the other, and that meets all the requirements of the ideal material. In this perspective, research for the development of biocompatible and bioinductive products, to be harnessed from natural sources, is encouraged. The objective of this study was to evaluate the responses of rats’ dental pulp, after the pulpotomy and protection of the remaining pulp tissue through a paste based on Anadenanthera colubrina (Vell.) Brenan and through the antibiotic paste CTZ, having calcium hydroxide as control for analysis. A total of 18 teeth, from 7 Wistar rats (Rattus norvegicus albinus), were divided into three groups: 1) A. colubrina bark extract + zinc oxide (1: 1) + polyethylene glycol 400, 2) PA calcium hydroxide + polyethylene glycol 400, 3) CTZ paste: tetracycline, chloramphenicol, zinc oxide (1: 1: 2) + eugenol. In addition, the four first molars from an extra animal were used, without intervention, as a histological pattern. 72 hours after pulpotomy, half of the animals were euthanized, their jaws and mandibles were dissected in blocks and processed for histological analysis. The same procedure was also done 15 days after pulpotomy with the remained animals. All histological sections were stained with hematoxylin and eosin (HE) and were morphologically evaluated, considering the degree of inflammatory infiltrate, pulp disorganization and formation of mineralized content. The morphological analysis revealed that the paste based on A. colubrina provided an intense inflammatory infiltrate and necrosis in the first 72 hours, with signs of remission and a tendency to deposit mineralized tissue in the period of 15 days. The samples treated with the CTZ paste showed intense inflammatory infiltrate, areas of necrosis and no evidence of deposition of mineralized tissue, in both evaluation periods. In the specimens treated with the calcium hydroxide paste, there was a slight inflammatory infiltrate, areas of necrosis, with underlying normal pulp tissue, within 72 hours; and intense deposition of mineralized tissue in the pulp exposure area within 15 days. None of the tested pastes showed the same or better results than those with calcium hydroxide paste, especially CTZ paste, which produced undesirable effects on pulp tissue in all analyzed samples. The results with the paste based on A. colubrina signaled a possible therapeutic potential as a pulp protection agent, however, further studies should be performed using standardized formulations.